2012
DOI: 10.1073/pnas.1200174109
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin 1 (Tmem16A) Ca 2 + -activated chloride channel stoichiometrically interacts with an ezrin–radixin–moesin network

Abstract: The newly discovered Ca 2+ -activated Cl − channel (CaCC), Anoctamin 1 (Ano1 or TMEM16A), has been implicated in vital physiological functions including epithelial fluid secretion, gut motility, and smooth muscle tone. Overexpression of Ano1 in HEK cells or Xenopus oocytes is sufficient to generate Ca 2+ -activated Cl − currents, but the details of channel composition and the regulatory factors that control channel biology are incompletely understood. We used a highly sensitive quantitative SILAC proteomics ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 43 publications
(57 reference statements)
5
139
0
Order By: Relevance
“…Our earlier findings suggested that Ano1 Cl 2 currents are controlled by the actin cytoskeleton [38]. This was supported by a subsequent report indicating that Ano1 associates with the signalling/scaffolding proteins ezrin, radixin, moesin and RhoA, which are known to connect plasma membrane proteins to the cytoskeleton [39]. Moreover, results from a two hybrid split ubiquitin screening suggested interaction of Ano1 with a number of proteins related to cell attachment and migration, such as zyxin, fibulin 1, S100A11, twinfilin and catenin (unpublished results from the Kunzelmann laboratory, K. Kunzelman 2012, figure 2).…”
Section: Role Of Ano1 For Metastasissupporting
confidence: 68%
“…Our earlier findings suggested that Ano1 Cl 2 currents are controlled by the actin cytoskeleton [38]. This was supported by a subsequent report indicating that Ano1 associates with the signalling/scaffolding proteins ezrin, radixin, moesin and RhoA, which are known to connect plasma membrane proteins to the cytoskeleton [39]. Moreover, results from a two hybrid split ubiquitin screening suggested interaction of Ano1 with a number of proteins related to cell attachment and migration, such as zyxin, fibulin 1, S100A11, twinfilin and catenin (unpublished results from the Kunzelmann laboratory, K. Kunzelman 2012, figure 2).…”
Section: Role Of Ano1 For Metastasissupporting
confidence: 68%
“…That the ChIMP method, which was previously developed in Ca V channels (39), is similarly effective in the unrelated TMEM16A/ 16B suggests that it may be generally applicable to the study and modulation of many different ion channel families. A recent quantitative proteomic approach revealed that TMEM16A is associated with a large network of intracellular proteins, many of which could be important for channel regulation (45). The ChIMP assay could be an invaluable tool for dissecting the functional relevance of other cytosolic proteins that putatively interact with TMEM16A intracellular domains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EGF stimulation has been shown to mediate calcium-activated chloride channel activation via activation of SRC (47) and to increase ANO1 expression in epithelial cells, suggesting a positive feedback mechanism between EGFR/SRC signaling and ANO1 (47,48). SRC recently has been shown to interact with ANO1 and can itself modulate the activation of EGFR, providing an additional explanation for the ANO1-dependent activation of EGFR signaling (49,50). EGFR is a known contributor to HNSCC, ESCC, and breast cancer tumorigenesis and is one the most important therapeutic targets in HNSCC.…”
Section: Ano1 Regulates Egfr-and Calcium-dependent Signaling Pathwaysmentioning
confidence: 99%